From metaverse experience to physical travel: the role of the digital twin in metaverse design - Deng, Baolin; Wong, IpKin Anthony; Lian, Qi Lilith (Tourism review (Association internationale d'experts scientifiques du tourisme), 2024)
Purpose Designing an effective metaverse experience through a tourism digital-twin platform is crucial to the success of metaverse tourism. How such a digital-twin platform should appeal to target users, however, lacks exploration. The study aims to advance a conceptual contribution by successfully creating a metaverse experience through a well-designed digital-twin platform. It also aims to show how the design science approach in tourism can enrich our understanding of digital-twin platform design elements introduced in metaverse experience design. Design/methodology/approach Guided by the design science approach in tourism, this research conceptualizes the role of digital-twin elements in metaverse experience design and proposes a one-factor between-subject experimental design to examine the effect. Findings This research conceptualizes how eight unique configurations of digital-twin design, which are embellished in two or three dimensions, shape tourists’ metaverse experience and physical travel intention. Practical implications The results offer operators clear strategic guidance on designing an effective tourism digital-twin platform. Originality/value This study not only identifies the impact of digital-twin platform design elements but also clarifies how such elements affect customers’ metaverse experiences. 从元宇宙体验到现实旅游: 数字孪生平台在元宇宙旅游设计中的作用 摘要 目的 通过旅游数字孪生平台设计有效的元宇宙旅游体验, 对元宇宙旅游的成功至关重要。然而, 这样一个旅游数字孪生平台应该如何吸引目标用户,还缺乏探索。该研究旨在通过精心设计的数字孪生平台成功塑造旅游者的元宇宙体验, 从而在概念上做出贡献。它还旨在展示旅游设计科学方法如何丰富我们对元宇宙体验设计中引入的数字孪生平台设计要素的理解。 设计/方法/途径 在旅游设计科学方法的指导下, 本研究将概念化数字孪生平台设计元素在元宇宙体验设计中的作用, 并提出了一个单因素的受试者间实验设计来检验效果。 研究结果 本研究将数字孪生平台设计的九种独特配置概念化, 这些配置在三个维度上得到了点缀, 塑造了游客的元宇宙旅游体验和现实旅游意向。 实践意义 研究结果为产业者设计有效的旅游数字孪生平台提供了明确的战略指导。 原创 现有的研究是第一个研究数字孪生平台设计元素的影响, 阐明了这些元素如何影响旅游者的元宇宙体验。 De la experiencia metaversal al viaje físico: El papel del gemelo digital en el diseño del metaverso Resumen Objetivo Diseñar una experiencia efectiva en el metaverso a través de una plataforma digital gemela de turismo es crucial para el éxito del turismo en el metaverso. Sin embargo, la exploración de cómo debería atraer dicha plataforma digital gemela a los usuarios objetivo carece de exploración. El estudio tiene como objetivo avanzar en una contribución conceptual al crear con éxito una experiencia en el metaverso a través de una plataforma digital gemela bien diseñada. También tiene como objetivo mostrar cómo el enfoque de la ciencia del diseño en el turismo puede enriquecer nuestra comprensión de los elementos de diseño de la plataforma digital gemela introducidos en el diseño de experiencias en el metaverso. Diseño/metodología/enfoque Guiada por el enfoque de la ciencia del diseño en el turismo, esta investigación conceptualiza el papel de los elementos gemelos digitales en el diseño de experiencias metaversales y propone un diseño experimental de un factor entre sujetos para examinar su efecto. Resultados Esta investigación conceptualiza cómo ocho configuraciones únicas de diseño gemelo-digital, enriquecidas en dos o tres dimensiones, conforman la experiencia metaversal de los turistas y su intención de viaje físico. Implicaciones prácticas Los resultados ofrecen a los operadores una orientación estratégica clara para diseñar una plataforma gemelo-digital turística eficaz. Originalidad/valor Este estudio no sólo identifica el impacto de los elementos de diseño de las plataformas gemelas digitales, sino que también aclara cómo afectan dichos elementos a las experiencias metaversales de los clientes.